Math problem solving in action : getting students to love word problems, grades 3-5 - Newton, Nicki (New York, NY : Routledge, 2017)
" ... Shows how make word problems more engaging and relatable, how to scaffold them and help students with math language, how to implement collaborative groups for problem solving, how to assess student progress ..." -- back cover.
Includes bibliographical references.
Keywords: Mathematics -- Study and teaching (Elementary); Word problems (Mathematics)